Exosomes released upon mitochondrial ASncmtRNA knockdown reduce tumorigenic properties of malignant breast cancer cells - Lorena González-sánchez; Rocío Bustos; América Campos; Valeria Silva; Verónica Silva; Emanuel Jeldes; Carlos Salomon; Manuel Varas-Godoy; Albano Cáceres-Verschae; Eduardo Duran; Tamara Vera; EZQUER, EDUARDO FERNANDO; et al. (My University, 2020)
AbstractDuring intercellular communication, cells release extracellular vesicles such as exosomes, which contain proteins, ncRNAs and mRNAs that can influence proliferation and/or trigger apoptosis in recipient cells, and have been proposed to play an essential role in promoting invasion of tumor cells and in the preparation of metastatic niches. Our group proposed the antisense non-coding mitochondrial RNA (ASncmtRNA) as a new target for cancer therapy. ASncmtRNA knockdown using an antisense oligonucleotide (ASO-1537S) causes massive death of tumor cells but not normal cells and strongly reduces metastasis in mice. In this work, we report that exosomes derived from ASO-1537S-treated MDA-MB-231 breast cancer cells (Exo-1537S) inhibits tumorigenesis of recipient cells, in contrast to exosomes derived from control-ASO-treated cells (Exo-C) which, in contrast, enhance these properties. Furthermore, an in vivo murine peritoneal carcinomatosis model showed that Exo-1537S injection reduced tumorigenicity compared to controls. Proteomic analysis revealed the presence of Lactadherin and VE-Cadherin in exosomes derived from untreated cells (Exo-WT) and Exo-C but not in Exo-1537S, and the latter displayed enrichment of proteasomal subunits. These results suggest a role for these proteins in modulation of tumorigenic properties of exosome-recipient cells. Our results shed light on the mechanisms through which ASncmtRNA knockdown affects the preparation of breast cancer metastatic niches in a peritoneal carcinomatosis model.
Keywords: animals; antigens, cd; antigens, surface; breast neoplasms; cadherins; carcinogenesis; cell line, tumor; cell movement; cell proliferation; exosomes; female; humans; mice; milk proteins; mitochondria; oligoribonucleotides, antisense; rna, untranslated; transplantation, heterologous; antisense oligonucleotide; cadherin; leukocyte antigen; membrane antigen; mfge8 protein, human; milk protein; untranslated rna; vascular endothelial cadherin; animal; breast tumor; carcinogenesis; cell motion; cell proliferation; drug effect; exosome; female; genetics; human; metabolism; mitochondrion; mouse; pathology; tumor cell line; xenograft